A Community and Medical Library Collaboration to Address Senior Caregivers Barriers to Health Services Access. Issue 2 (3rd April 2018) - Henner, Terry
ABSTRACT: This describes an outreach program to improve access to community resources and online health information for the lay public and professionals engaged in caregiving to seniors. An academic health sciences library and a coalition of community organizations collaborated to develop an authoritative, web-enabled clearinghouse that consolidated access to regional and national health and social service resources and online health information. Findings from a mixed-methods approach of roundtable discussions, key informant structured interviews, and surveys of professionals involved in senior care planning and discharge management were used to develop, pilot test, and evaluate the project. The website was promoted through a series of webinars outlining the range of services and resources available as well as engagement with a variety of community health care organizations. This project advanced understanding of the needs of seniors and their caregivers and created mechanisms to improve access to authoritative health care information supporting senior care. Community feedback on the website launch highlights its value for the lay public and professional caregivers. It also provided a platform for volunteerism and service learning through which individuals can have a collective impact on their community.